Migration and loving - Deniz Gevrek (Institute for the Study of Labor (IZA), 2010)
This paper explores the relationship between anti-miscegenation laws, interracial marriage and black males' geographical distribution in the U.S. during and after the Great Migration. The U.S. Supreme Court decision in the case of Loving v. Virginia in 1967, which forced the last 16 Southern states to strike down their anti-miscegenation laws, creates a unique opportunity to explore the impact of an exogenous change in a state's laws regulating interracial marriages. Analyzing the U.S. Census data, I find that anti-miscegenation laws in an individual's state of birth affect the sorting of inter- and intraracially married black males into destination states differentially.
Keywords: J12; J15; 330; interracial marriage; migration; anti-miscegenation laws; Ethnische Beziehungen; Ehe; Soziale Beziehungen; Binnenwanderung; Farbige Bevölkerung; Räumliche Verteilung; USA